Nuclear Spins in a Solid Exceeding 10-Hour Coherence Times for Ultra-Long-Term Quantum Storage - Fudong Wang; Miaomiao Ren; Weiye Sun; Mucheng Guo; Matthew J. Sellars; Rose L. Ahlefeldt; John G. Bartholomew; Juan Yao; Shuping Liu; Manjin Zhong (PRX Quantum)
Long-term quantum storage for quantum communication applications will require optically accessible states with coherence times exceeding the desired storage time. Ground-state hyperfine levels in Eu^{3+}:Y_{2}SiO_{5} have previously shown coherence times as long as 6 h at 1.4 K when operated at a zero-first-order-Zeeman (ZEFOZ) point. Here, we have characterized the limiting decoherence mechanisms acting in this regime, which shows that the coherence time is limited by the presence of spin impurities. This dephasing effect has been suppressed by cooling the sample to 125 mK, resulting in an extension in the coherence time to over 13 h. In the absence of these impurities, the dominant source of dephasing is the field inhomogeneity of the ZEFOZ point arising from the spin inhomogeneous broadening. We have shown that coherence times over 18 h can be achieved by operating using a spectrally narrow subensemble selected from within the inhomogeneous line. The observed coherence time is longer than that of any other system suitable for an optical quantum memory. Furthermore, at a much higher temperature of 6 K, we have realized a 6-h coherence time, which has been obtainable using single-stage cryocoolers. These results imply advanced engineering feasibility in designing and operating future quantum information-storage devices for a wide range of applications, including in satellites.